2005
DOI: 10.1002/lt.20401
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of the pediatric end‐stage liver disease scoring system: A single center experience

Abstract: The Pediatric End-Stage Liver Disease (PELD) scoring system is a new nationally utilized formula developed to provide a continuous numerical assessment of the risk of death in order to allocate livers to children for transplantation. A retrospective review of the clinical course of children undergoing liver transplantation at the Mount Sinai Medical Center was performed in order to assess the effectiveness of this scoring system in the first 24 months of its utilization. Forty-eight patients underwent liver tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 9 publications
(18 reference statements)
4
45
0
Order By: Relevance
“…If we wish to change this high rate, several potential contributing factors will need to be examined to determine causes and possible solutions: (1) etiology of liver failure; (2) timing of referral for transplantation; Concerns have been raised about the ability of the PELD score to reliably prioritize children for liver transplantation (20,21). Also, the correlation with MELD scores may be imprecise, making it difficult for children to compete with adult candidates for organs (20,21). Both of these factors have been felt to disadvantage certain candidates in terms of timely access to a liver allograft.…”
Section: Liver Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…If we wish to change this high rate, several potential contributing factors will need to be examined to determine causes and possible solutions: (1) etiology of liver failure; (2) timing of referral for transplantation; Concerns have been raised about the ability of the PELD score to reliably prioritize children for liver transplantation (20,21). Also, the correlation with MELD scores may be imprecise, making it difficult for children to compete with adult candidates for organs (20,21). Both of these factors have been felt to disadvantage certain candidates in terms of timely access to a liver allograft.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…A number of publications have voiced concern that the present allocation system is not serving children well (20,21,23), but pediatric pretransplant death rates have not risen with the introduction of MELD/PELD nor with any of the subsequent policy modifications. It is possible that the candidates who die on the waiting list may have changed in terms of the severity of diagnosis or geographical distribution from those who died waiting during the pre-MELD era.…”
Section: New Status 1 Criteria (Optn Policy 3642)mentioning
confidence: 99%
See 1 more Smart Citation
“…Children with a PELD greater than 12 ( n = 47) had a higher rate of post-LT mortality and retransplantation than those with a PELD of 10 or less. The authors suggested that a PELD score approaching 10 should trigger discussion of LT. PELD is the only scoring system currently used in children and although helpful in advanced liver dysfunction; it is of limited value in the very young (under 1 year of age) and in older recipients, particularly with complications such as recurrent cholangitis, severe portal hypertension, pulmonary hypertension, and hepatopulmonary syndrome [25][26][27][28][29]. Because of these limitations, PELD use has been largely restricted to North America.…”
Section: Timing Of Transplantationmentioning
confidence: 99%
“…However, many publications have shown that the PELD system is not an accurate reflection of the degree of illness for most of the children waiting for LT [1,2]. Furthermore, disparities in the current organ allocation system in the USA have been proven [3••].…”
Section: Timing Of Liver Transplantationmentioning
confidence: 99%